Betrayal Recovery in The Girl on The Train by Paula Hawkins (2015) - Nada Nyata Pasti; Desvalini Anwar (Universitas Negeri Padang, 2023)
This research is an analysis of the novel by Paula Hawkins entitled The Girl on The Train (2015). This research reveals the kinds of betrayals committed by Rachel's ex-husband and how she was able to manage her life after experiencing trauma, anxiety and depression for a long time. This research is a qualitative descriptive study that uses psychoanalysis theory and is supported by defense mechanism theory. The results of this research indicate several stages that Rachel went through to be able to rise from the adversity she experienced. The stages of recovering the betrayal that are told in this novel are; denial, anger, depression, bargaining and acceptance. These stages have a different time span for each victim, depending on the betrayal experienced and the mental state of each victim. The results of this study also reveal that betrayal can occur not because of the shortcomings and helplessness of the betrayed person, but betrayal can occur purely because the traitors do not have the value of loyalty in themselves. Therefore, no matter how perfect their partner is, traitors will never be satisfied.